The role of the pulsed-wave laser characteristics on restraining hot cracking in laser cladding non-weldable nickel-based superalloy. (15th January 2021) - Zhang, Zhenlin; Zhao, Yue; Chen, Yang; Su, Zhen; Shan, Jiguo; Wu, Aiping; Sato, Yutaka S.; Gu, Huaipeng; Tang, Xin
Abstract: A paraxial powder-feeding system by employing a quasi-continuous fiber laser machine was established to repair non-weldable nickel-based K447A alloy. In the present study, the duty cycle (DC) of the pulsed-wave laser was chosen to reveal the influence on hot cracking. The results showed that the total length of hot cracking on the 10.5 mm-length longitudinal section of the cladding zone reduces from 3.263 mm to 0.092 mm with the decline of DC from 80% to 30%. The intermittent occurrence of the laser beam induced the ripple microstructure in the cladding layer (CL). It is the high cooling rate in laser extinguishment process that caused the fine dendrite zone which provides more resistance for hot cracking propagation in the CL. The liquid film in the heat-affected zone (HAZ) mainly results from the M5 B3 /γ, γ′/γ, and MC/γ constitutional liquation successively among 1200–1300 °C. Heat input is the main factor affecting hot cracking in the HAZ. With the decrease of DC, the dendrite spacing of the fine dendrite zone decreases in the CL, and the depth of liquefaction zone decreases in the HAZ, as a result, the length of hot cracking in the CL and HAZ both decreases. Graphical abstract: Unlabelled Image Highlights: Duty cycle of the pulsed-wave laser was chosen to reveal the influence on hot cracking. The influence of ripple characteristics on hot cracking propagation in the cladding layer was revealed. The intergranular liquation mechanism of a non-weldable nickel-based alloy was clarified as detailed.